Relationship of BMI with Severity of Chronic Obstructive Pulmonary Disease (COPD): Body Mass Index with Chronic Obstructive Pulmonary Disease - Javed, Izzah; Javed, Azka; Zafar, Zaryan; Uzair, Ahmed; Din, Hafiz Kamal; Riaz, Maryam (Pakistan Journal of Health Sciences, 2025)
COPD is linked to significant extra-pulmonary manifestations. However, limited research exists on relationship between BMI and COPD severity. Objective: To find frequency of COPD stages and to compare mean BMI in various stages of COPD. Methods: This cross-sectional study was conducted at Chest Medicine Department, Mayo hospital, Lahore from August 2022, to February 2023 after approval of synopsis from CPSP. 160 COPD patients were enrolled, and classification as per GOLD guidelines and BMI was calculated. Data were analyzed using SPSS version 26.0, comparison of BMI across COPD stages was done using ANOVA and post Hoc analysis done, p-value ≤ 0.05 considered statistically significant. Results: Among 160 individuals, 26.2% had COPD Stage I, 23.8% had stage II, while Stage III and IV observed in 25% each. Mean BMI was 24.30 ± 2.71, 25.86 ± 5.77, 20.29 ± 5.39, and 19.50 ± 6.07 in Stage I-IV, P<0.001. Mean BMI difference was statistically significant when comparing Stage, I vs. III (p = 0.003), Stage I vs. IV (p < 0.001), Stage II vs. III (p < 0.001), and Stage II vs. IV (p < 0.001). However, difference between Stage III and IV was not statistically significant (p = 0.900). Conclusions: The distribution of COPD severity was relatively even across all stages, with comparable proportion of patients in each stage. A significant decline in BMI was observed with increasing disease severity. These findings emphasize the importance of regular BMI monitoring in COPD patients, as lower BMI is linked to disease progression and poorer clinical outcomes.